Productivity and Nutrient Digestibility of Sorghum Fodder at Different Urine Fertilizers Levels and Harvest Times - Harwanto Harwanto; Eko Hendarto; Bahrun Bahrun; Nur Hidayat; Dina Istiqomah; Dewi Puspita Candrasari (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2022)
The present study aimed to determine the productivity and nutrient digestibility of sorghum (Sorghum bicolor (L.) Moench) fodder given different levels of urine fertilizer in various planting media and harvest times. The study was carried out in June - September 2020 and used numbu variety of sorghum planted hydroponically at fodder phase. This study used a 2x4 factorial completely randomized design with 4 replications. The first factor was the harvest time at 5 days (H1) and 10 days (H2). The second factor was the planting media that included water medium as an internal control (M1), 12.5 mL/L of urine fertilizer (M2) and 25 mL/L of water medium (M3), and urea 20 mg/L of water medium (M4) as the external control. The urine fertilizer was derived from Ongole crossbreed urine fermented for 21 days. The density of sorghum seeds in the planting medium was 2.5 kg/m2. The observed variables included plant productivity and nutrient digestibility in vitro. Data analysis used ANOVA and continued with Duncan's Multiple Range Test to determine significance. The results showed that the addition of urine fertilizer and harvest time had a significant effect on plant height, length of fresh leaf production, dry matter, organic matter, and crude protein compared to those of the internal control. The H2M3 treatment provides a comparable productivity effect with H2M4. Meanwhile, harvest time affected dry matter and organic matter digestibility. It can be concluded that 25.0 mL/L of urine fertilizer in planting medium and harvest time in 10 days were able to increase productivity, dry matter digestibility, and organic matter digestibility of sorghum fodder.